Boosting Union Membership: Reconciling Liberal and Social Democratic Conceptions of Freedom of Association via a Union Default. (10th September 2020) - Harcourt, Mark; Gall, Gregor; Novell, Nisha; Wilson, Margaret
Abstract: Deploying insights from legal experts in New Zealand, this article examines how a union default could strengthen unions and boost their membership, while reconciling conflicting liberal and social democratic conceptions of freedom of association. The insights are used to develop a broad framework by which a default system could work both in New Zealand and more generally. These insights are then applied to the case of Britain, wherein components of the institutional architecture, embodied in Schedule A1 of the Employment Relations Act 1999, could be appropriately amended.